Factors influencing career competencies among youth in Malaysia / Nur Amira Mhd Amer and Siti Rahmas Abit - Mhd Amer, Nur Amira; Abit, Siti Rahmas (2015)
This research was conducted to carry out a study of “Factors influencing career competencies among youth in Malaysia”. Generally, three independent variables were identified in this research which is knowledge skill, functional skill, and social skill. For this study, 150 youth in Selangor were chosen as respondents. In this research, researchers conducted quantitative research. While the nature of the study was causal study and the unit of analysis is individual focus on youth in Selangor. The data obtained from primary data by using questionnaire. All data collected through the questionnaire were analysed systematically by Statistical Package for Social Science (SPSS). From the finding, the result show three independent variables which are Knowledge Skill, Functional Skill, and Social Skill have strong relationship with career competencies among youth in Malaysia and the most significant predictor variable is knowledge skills. Overall, the researchers are able to answer all research objectives.